IMPLEMENTATION OF BRAINSTORMING BASED ON LEARNING CYCLE 5-E MODEL TO COMPLETE STUDENT LEARNING OUTCOME OF X-SCIENCE STUDENTS ON THE MATERIAL OF ELECTROLYTE AND NONELECTROLYTE SOLUTION IN SMAN 1 SIDOARJO (Universitas Negeri Surabaya, 2018)
Abstract This research aims to describe the learning implementation and student activity during the implementation of Brainstorming based on Learning Cycle 5-E model, and student learning outcome mastery after the implementation of Brainstorming based on Learning Cycle 5-E model on the material Electrolyte and Nonelectrolyte Solution. Type of this research was pre-experiment research with used “One-Group Pretest-Posttest Design”. The subjects of this research were students of class X-Science SMAN 1 Sidoarjo academic year 2017-2018 which amounted to 36 students. The results of this research indicate that the implementation of Brainstorming based on Learning Cycle 5-E model was very good with average quality on the first meeting of 3.63 (very good) and the second meeting of 3.83 (very good). Percentage of students activity time that spent on Brainstorming activities was 22.5%, 70% relevant activities and 7.5% non-relevant activities. Students learning outcomes before being treated (pretest) on the materials of Electrolyte and Nonelectrolyte Solutions are 0% to achieve individual mastery, but the learning result after being treated (posttest) on Electrolyte and Nonelectrolyte Solutions has reached 100% classical mastery. Thus, the implementation of Brainstorming based on Learning Cycle 5-E model can mastery student learning outcomes on the Electrolyte and Nonelectrolyte Solutions material. Keywords: Learning Cycle 5-E, Brainstorming, Learning Outcome.